2014
DOI: 10.5194/acp-14-719-2014
|View full text |Cite
|
Sign up to set email alerts
|

Campholenic aldehyde ozonolysis: a mechanism leading to specific biogenic secondary organic aerosol constituents

Abstract: Abstract. In the present study, campholenic aldehyde ozonolysis was performed to investigate pathways leading to specific biogenic secondary organic aerosol (SOA) marker compounds. Campholenic aldehyde, a known α-pinene oxidation product, is suggested to be a key intermediate in the formation of terpenylic acid upon α-pinene ozonolysis. It was reacted with ozone in the presence and absence of an OH radical scavenger, leading to SOA formation with a yield of 0.75 and 0.8, respectively. The resulting oxidation p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 59 publications
9
38
0
Order By: Relevance
“…Their analysis showed two structurally different carboxylic acid species -a hydroxyl-acidic ester as well as a peroxyacetyl carboxylic acid. It is also of interest that one recurring molecular formula in all OH/NO x samples is that of C 9 H 13 O 7 N. Assuming that it is a nitric acid ester (ROH + HONO 2 → RONO 2 + H 2 O), the unesterified compound would have the formula C 9 H 14 O 5 , a compound observed in APIN, BPIN, HUM, MYR, and TMB OH/NO x samples in this study as well as in ozonolysis of alpha-pinene, 68 limonene, 69,70 campholenic aldehyde 65 in previous studies. It is not clear how the C 9 H 13 O 7 N could be formed from the aromatic precursors; however, we cannot exclude the possibility that its occurrence in all samples is an experimental artifact from "carry-over" between SOA generated from different precursors on different days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis showed two structurally different carboxylic acid species -a hydroxyl-acidic ester as well as a peroxyacetyl carboxylic acid. It is also of interest that one recurring molecular formula in all OH/NO x samples is that of C 9 H 13 O 7 N. Assuming that it is a nitric acid ester (ROH + HONO 2 → RONO 2 + H 2 O), the unesterified compound would have the formula C 9 H 14 O 5 , a compound observed in APIN, BPIN, HUM, MYR, and TMB OH/NO x samples in this study as well as in ozonolysis of alpha-pinene, 68 limonene, 69,70 campholenic aldehyde 65 in previous studies. It is not clear how the C 9 H 13 O 7 N could be formed from the aromatic precursors; however, we cannot exclude the possibility that its occurrence in all samples is an experimental artifact from "carry-over" between SOA generated from different precursors on different days.…”
Section: Resultsmentioning
confidence: 99%
“…62 Another molecular formula, C 9 H 14 O 3 , identified as ketolimononaldehyde in limonene SOA, 63 is also appearing in all the O 3 samples. Other common formulas observed in all O 3 and all OH/NO x samples include C 10 H 14 O 5 , possibly peroxo-pinic acid or its isomer, 64 previously observed in α-pinene ozonolysis as well as campholenic aldehyde ozonolysis, 65 and C 10 H 16 O 6 , which has been potentially identified as an ester of glutaric acid or 5-hydroxy-pentanoic acid as seen in the study of ozonolysis of cyclohexene by Hamilton et al 66 A study of the ozonolysis of α-pinene and limonene by Warscheid and Hoffmann 67 also identified the molecular formula of C 10 H 16 O 6 through an online MS n technique. Their analysis showed two structurally different carboxylic acid species -a hydroxyl-acidic ester as well as a peroxyacetyl carboxylic acid.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed previously, MBTCA and terebic acid will be formed from the OH-initiated oxidation of pinonic acid and terpenylic acid, respectively. Kahnt et al (2014) suggested that C 9 H 14 O 5 as well as C 9 H 14 O 6 formed from the ozonolysis of campholenic aldehyde were C9-carbonyl-dicarboxylic acid and C9-tricarboxylic acid, respectively. As campholenic aldehyde is formed from the heterogeneous oxidation of a-pinene, C9-carbonyl-dicarboxylic acid and C9-tricarboxylic acid will also be formed from the ozonolysis of a-pinene.…”
Section: Time Series and Oh Exposurementioning
confidence: 98%
“…Here the reaction of ozone and α-pinene leads to the formation α-pinene oxide which can rearrange to campholenic aldehyde. Once formed, campholenic aldehyde may undergo further reaction with ozone to form terpenylic aldehyde, which can then be further oxidized in the particle phase to form terpenylic acid (Iinuma et al, 2013;Kahnt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%